2012
DOI: 10.1242/jeb.073833
|View full text |Cite
|
Sign up to set email alerts
|

Limb force and non-sagittal plane joint moments during maximum-effort curve sprint running in humans

Abstract: SUMMARYCompared with running straight, when human runners sprint along a curve, the ability of the inside leg to generate force is compromised. This decreased force generation has been suggested to limit the overall performance of the runner. One theory for this force loss is that the large non-sagittal plane joint moments of the inside leg reach their operating limits, thus prohibiting further generation of the performance-related sagittal plane joint moments. We investigated the inside leg force generation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…But, stride frequency data for sprinters with a leg amputation do not indicate clear stride frequency enhancements Kram et al, 2010). In addition, RSP are torsionally stiff and resist inversion/eversion, which may impede the optimal inversion and eversion necessary for unbanked curve running (Greene, 1987;Luo and Stefanyshyn, 2012). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But, stride frequency data for sprinters with a leg amputation do not indicate clear stride frequency enhancements Kram et al, 2010). In addition, RSP are torsionally stiff and resist inversion/eversion, which may impede the optimal inversion and eversion necessary for unbanked curve running (Greene, 1987;Luo and Stefanyshyn, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…However, because it is difficult to motivate and control the behavior of non-human animals, human running experiments have provided a practical test-bed for exploring the biomechanics of high-speed locomotion on curves. In humans, compared with straight running, maximum running speed is slower on unbanked curves and related to curve radius (Chang and Kram, 2007;Churchill et al, 2015;Ferro and Floria, 2013;Greene, 1985;Luo and Stefanyshyn, 2012). For example, human maximum speed on a 6 m radius unbanked curve is ∼26% slower than straight running (Chang and Kram, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The results of Luo and Stefanyshyn [24] did not support either of the aforementioned theories on the limitations of curved sprinting performance. Instead, their results indicated that the sagittal plane ankle joint moments may be the limiting factor, as the ankle plantarflexion moment did not change even with the presence of the additional mass.…”
Section: Outsole Tractionmentioning
confidence: 73%
“…Previous research has also reported this finding [25] and it has been shown that during running, the soleus and gastrocnemius muscles are the primary contributors to the ankle joint [26]. During curved running, the inside foot was in an everted position during the stance phase [24] and it has been speculated that as the ankle joint moves away from its neutral alignment (into eversion or inversion), its ability to generate force decreases. Pilot testing was therefore conducted to determine if ankle plantarflexor force was restricted as the ankle joint entered eversion or inversion.…”
Section: Outsole Tractionmentioning
confidence: 75%
See 1 more Smart Citation